2015
DOI: 10.1007/s00415-015-7731-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting prognosis in amyotrophic lateral sclerosis: a simple algorithm

Abstract: The objective of the study was to develop and validate a practical prognostic index for patients with amyotrophic lateral scleroses (ALS) using information available at the first clinical consultation. We interrogated datasets generated from two population-based projects (based in the Republic of Ireland and Italy). The Irish patient cohort was divided into Training and Test sub-cohorts. Kaplan–Meier methods and Cox proportional hazards regression were used to identify significant predictors of prognoses in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 35 publications
7
73
1
Order By: Relevance
“…Slopes were calculated using the common convenience method for calculating ALSFRS-R slope=(48—ALSFRS-R/time from onset) based on the first ALSFRS-R for each person, as this methodology has been reported in prognostic models8 9 and can be calculated from a single score. This method was extended to produce convenience estimates for ALSFRS-R_bulb, ALSFRS-R_motor and ALSFRS-R_resp slopes.…”
Section: Methodsmentioning
confidence: 99%
“…Slopes were calculated using the common convenience method for calculating ALSFRS-R slope=(48—ALSFRS-R/time from onset) based on the first ALSFRS-R for each person, as this methodology has been reported in prognostic models8 9 and can be calculated from a single score. This method was extended to produce convenience estimates for ALSFRS-R_bulb, ALSFRS-R_motor and ALSFRS-R_resp slopes.…”
Section: Methodsmentioning
confidence: 99%
“…Further, most use a Cox's proportional hazards model; in a similar study of mortality in ALS,10 the use of such a model was examined and found to be ‘clearly inadequate’, as the effects of predictors including riluzole use were found to vary with time from diagnosis, violating the proportional hazards assumption. We know of only two explicit predictive models, of which one11 requires data which would not usually be available in the clinic, and the other12 omits important predictors.…”
Section: Introductionmentioning
confidence: 99%
“…Female sex, higher diagnostic certainty, lower score on the ALS Functional Rating Scale, and greater rate of disease progression after diagnosis may be associated with a worse prognosis, but the associations are less consistent (5)(6)(7)(8). More recently, rate of decline of ALS functional rating score before diagnosis and executive dysfunction have also been discussed as predictors of poor prognosis for ALS (9).…”
mentioning
confidence: 99%